The Effect of Incorporation Kappa-Carrageenan Powder on the Physical and Mechanical Properties of the Heat-Cured Acrylic-based Soft Denture Lining Material in Clinical Use - Hiba A. Salih1 , Faiza M. Abdul-Ameer2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Soft denture relining materials have been introduced to prosthetic dentistry since long timeto improve the patient’s acceptance to dental prosthesis. However, with the growing need to provide thepatients with dentures that have improved comfort and masticatory efficiency, there is a growing demand toimprove several features of the denture lining materials. Therefore, the aims of this study was to evaluatethe effect of incorporation kappa-carrageenan powder as antifungal agent on the hardness and peel bondstrength of the heat-cured acrylic-based soft denture lining material.Materials and Methods: Two percentages of kappa-carrageenan powder (1.5wt.% and 2wt.%) have beenselected based on the pilot study that produced the best antifungal effect. A total of sixty samples wereprepared and divided into three equal groups groupA:0.0wt.%, groupB:1.5wt.%, groupC:2wt.% of kappacarrageenan powder additive. Each group was further subdivided into two equal groups for shore-A hardnesstest and peel bond strength test. Fourier transform infrared spectroscopy (FTIR) analysis was performed toinvestigate if there is any chemical reaction between the soft lining material and the kappa-carrageenanpowder, scanning electron microscope (SEM) was used to determine the distribution of kappa-carrageenanpowder in the soft liner matrix.Results: All the resulted data were analysed using “one-way analysis of variance (ANOVA) and DunnetT3 post-hoc test at a significance level of p<0.05”. The result of shore-A hardness test revealed significantincrease (P<0.05) in the values of hardness of both experimental groups (B and C) when compared with thecontrol group(A). Peel bond strength test revealed non-significant decrease (P>0.05) in the values of peelbond strength for experimental group(B), while there was significant decrease (P<0.05) for the experimentalgroup(C) when compared to the control group. FTIR analysis showed no difference in the spectra betweencontrol group and experimental group this means that there is no chemical interaction between the twomaterials. SEM test results showed a degree of agglomeration of the kappa-carrageenan powder into the softliner matrix.Conclusion: Adding kappa-carrageenan powder to the soft liner affected the physical and mechanicalproperties of the lining material and the most adverse effect was noted for the group C(2 wt.%) but all effectswas in the acceptable range for clinical use.